Pemetaan Sistem Monitoring Keragaan Produksi Berbasis Blok - Ihsan, Fahmi; Yuniasih, Betti; Wirianata, Herry (Program Studi Agroteknologi INSTIPER, 2024)
achieving palm oil productivity. Monitoring of production achievement is visualized in a map. The purpose of this study is analyze spatially and temporally of achieving palm oil productivity. Productivity achievement are calculated from the percentage of actual productivity against the company's plan production from 2016 - 2020. Oil palm plantation blocks with high production achievements (>90%) are visualized in green, medium production (70-89%) are visualized in yellow, and low production (<70%) are visualized in red. This research was conducted at Sepantaian Estate of PT. Bumitama Gunajaya Abadi, Kotawaringin Lama District, West Kotawaringin Regency, Central Kalimantan Province, in August - October 2022. The Sepantaian Estate oil palm plantation production achievement map can visualize data spatially on the condition of the 4 Divisions and temporally visualize the condition of production achievement in 2016-2020. The temporal map of palm oil production achievements shows that the lowest production achievements occurred in 2016 and the highest production achievements in 2020. Spatially, it is known that Division III is the division with the lowest production achievements in 2016 and 2017. Maps of oil palm plantation production achievements can be used for monitoring, evaluation and input to plantation management in making decisions in managing oil palm plantations.